High Schools’ Students Mathematics Communication Ability: Learning Style Perspective - Meyta Krisdianti; Prayogo Prayogo (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
Students' mathematical communication is a mutual method of various mathematical inspirations that are learned and clarified through understanding. Communication of mathematical ideas can be used as objects of reflection, and can be replaced, can be improved, and can be discussed. This study intends to identify students' communication ability in terms of visual, auditory, and kinesthetic learning styles. This qualitative descriptive study involved 25 students of class VIII-C in SMP 17 August 1945 Surabaya. The instruments used in this study include a learning style questionnaire, mathematical communication test, and interviews. The result is that students' mathematical communication ability in terms of auditory learning styles are capable of indicators express known information and asked information, using mathematical icon, drawing shape, and planning get solution. Likewise, students' mathematical communication ability in terms of visual learning styles can be in indicators express known information and asked information, then planning get solution. On the other hand, students' mathematical communication ability in terms of kinesthetic learning styles are capable of indicators express known information, planning get solution, and conclude.